2022
DOI: 10.3390/molecules27248742
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition Profiling and Antifungal Activity of Saffron Petal Extract

Abstract: Numerous fungal plant pathogens can infect fresh fruits and vegetables during transit and storage conditions. The resulting infections were mainly controlled by synthetic fungicides, but their application has many drawbacks associated with the threatened environment and human health. Therefore, the use of natural plants with antimicrobial potential could be a promising alternative to overcome the side effects of fungicides. In this regard, this study aimed at evaluating the antifungal activity potential of saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Possibly higher concentrations may demonstrate inhibition activity against this strain, which leads to the possibility of future work. The same was observed in studies by Naim et al (2022), where they also found an inhibition effect on R. stolonifer and Penicillium digitatum evaluating the extract of C. sativus petals with the lowest concentration of 10% and for Botritys cinerea with 5% concentration where there was inhibition of mycelial and spore germination of 100%. Ali et al (2020) also verified the potential suitability for the floral extract of Tagetes erecta on the phytopathogenic fungus Fusarium verticillioides with inhibition between 44-65%.…”
Section: Discussionsupporting
confidence: 81%
“…Possibly higher concentrations may demonstrate inhibition activity against this strain, which leads to the possibility of future work. The same was observed in studies by Naim et al (2022), where they also found an inhibition effect on R. stolonifer and Penicillium digitatum evaluating the extract of C. sativus petals with the lowest concentration of 10% and for Botritys cinerea with 5% concentration where there was inhibition of mycelial and spore germination of 100%. Ali et al (2020) also verified the potential suitability for the floral extract of Tagetes erecta on the phytopathogenic fungus Fusarium verticillioides with inhibition between 44-65%.…”
Section: Discussionsupporting
confidence: 81%
“…The mechanisms of action by which plant extracts suppress the growth of microbial pathogenes are multiple and include disruption of cell membrane function, disruption of energy activity, and damage to the cytoplasmic membrane [42]. In addition, these samples have been shown to possess antioxidant activity [43]. According to Rice-Evans et al and She et al [44,45], the antioxidant capacity of plant extracts is closely associated with phenolic components, which could interact with the free radicals by electrons or hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional fungicide methods of controlling postharvest fruit diseases increase pathogen resistance and threaten food safety and the environment [3][4][5]. In recent decades, the research landscape has shifted towards exploring natural antimicrobials, specifically leveraging plant secondary metabolites as viable alternatives [6]. In plants, a remarkable phenolic-ester-based defense system has evolved and serves as a safeguard against a range of environmental stressors, encompassing drought conditions and pathogenic bacterial infestations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%